What do Cochrane Systematic Reviews say about conservative and surgical therapeutic interventions for treating rotator cuff disease? : Synthesis of evidence - Franco, Eduardo Signorini Bicas; Puga, Maria Eduarda dos Santos; Imoto, Aline Mizusaki; Almeida, Jhony de; Mata, Vitor da; Peccin, Stella (São Paulo Medical Journal, 2019)
BACKGROUND: Shoulder pain is considered to be the third largest cause of musculoskeletal functional alterations in individuals presenting pain during movement. OBJECTIVE: The purpose of this synthesis of evidence was to identify the clinical effectiveness of con-servative and surgical treatments reported in Cochrane systematic reviews among individuals diagnosed with rotator cuff disease. DESIGN AND SETTING: Review of systematic reviews, conducted in the Federal University of São Paulo (Universidade Federal de São Paulo, UNIFESP). METHODS: This synthesis of evidence included systematic reviews that had been published in the Co-chrane database. The inclusion criteria were that these systematic reviews should involve individuals aged ≥ 16 years with rotator cuff disease, comparing surgical procedures with or without associated nonsurgical procedures versus placebo, no treatment or other nonsurgical interventions. RESULTS: Thirty-one systematic reviews were included, involving comparisons between surgical procedures and conservative treatment; procedures either combined or not combined with drugs, versus other proce-dures; and procedures involving exercises, manual therapy and electrothermal or phototherapeutic resources. CONCLUSIONS: The findings suggest that strengthening exercises, with or without associated manual therapy techniques and other resources, were the interventions with greatest power of treatment over the medium and long terms, for individuals with shoulder pain. These had greater therapeutic power than surgical procedures, electrotherapy or photobiomodulation. PROTOCOL REGISTRATION NUMBER IN THE PROSPERO DATABASE: ID - CRD42018096578.